Chronic corticosterone exposure disrupts hepatic and intestinal bile acid metabolism in chicken - Wu, Lei; Liu, Xinyi; Zhang, Aijia; Chen, Huimin; Zhao, Ruqian; Jia, Yimin (Frontiers in Veterinary Science, 2023)
Objective: Studies showed that chronic stress leads to a high circulating level of glucocorticoid, which disrupts lipid metabolism and causes fatty liver in chickens. Bile acid (BA), a class of metabolites initially synthesized in the liver and further metabolized by gut microbiota, plays a vital role in lipid metabolism. This study aimed to investigate the effects of glucocorticoids on BA metabolism and gut microbiota. Methods: In this study, 35-day-old chickens were injected with 4 mg/kg/day corticosterone (Cort) for 14 days to simulate chronic stress. Results: Cort treatment significantly increased the triglyceride contents in plasma and the liver. Histological and oil-red staining showed that Cort treatment induced fatty liver in chickens. Meanwhile, Cort exposure downregulated the liver's total bile acid (TBA) content while increasing the TBA in feces. UPLC-HRMS results showed that Cort exposure significantly decreased the hepatic levels of CDCA, T-alpha-MCA, and T-beta-MCA. Moreover, Cort exposure significantly reduced the expression of genes related to BA synthesis (CYP8B1, CYP27A1), conjugation (BACS), and regulation (KLβ and FGFR4). 16s sequencing results showed that Cort treatment significantly decreased the amount of Lachnospiraceae, Eisenbergiella, Blautia, and Eubacterium and increased the abundance of Barnesiella, Lactobacillus, and Helicobacter. Spearman correlation analysis showed a significant positive correlation between fecal TBA and the abundance of Lactobacillales, Lactobacillus, and Barnesiella. In comparison, TBA in the liver was positively correlated with Eubacterium, and negatively correlated with Helicobacter. Conclusion: In summary, Cort exposure altered the gut microbiota composition, which might attenuate the hepatic BA synthesis. The interaction between the gut microbiome and bile acid under Cort treatment was associated with the development of fatty liver in chickens.